Efektifitas Crossword Puzzle Braille Untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Pada Siswa Tunanetra Sekolah Luar Biasa Negeri Batam - Alifia Deviyanti; Miftahul Apriliana; Ivanika Satria; Adam adam (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The State Special School Batam is a state school for elementary school to high school for people with disabilities, which is located in the center of Batam city. In the teaching and learning process, English is not included in the curriculum and certainly not used as a compulsory subject. This is caused by the lack of teaching staff's number, especially the blind teaching staff, lack of facilities, and lack of motivation from the students themselves. In fact, students with special disabilities are also entitled to receive the same teaching regarding to language skills. Therefore, the researcher provides a solution in the form of using Crossword Puzzle Braille as a medium to learn vocabulary in English. Crossword Puzzle Braille is a Braille-based crossword puzzle game intended for students with visual impairments. By combining the play and learn elements, it is hoped that students will be more interested in learning. The researcher conducted a pretest and posttest by giving a questionnaire containing 6 indicators; Days of a week, Family members, Basic Color, Body Part, Animals, and Number 1 to 10. The results of the comparison of pretest and posttest showed a significant increase. The pretest result showed 15% and the posttest result after 1 month of learning process using Crossword Puzzle Braille showed 48.17%. This shows that Crossword Puzzle Braille is effective for improving vocabulary mastery of blind students at The State Special School of Batam.